Study on the Optimal Interval of Monitoring Following Gastric Polyp. Issue 2 (2000) - Kawaguchi, Minoru; Saito, Toshihiko
Abstract : The present study was conducted to determine how long hyperplastic polyps (HPs) and fundic gland hyperplastic polyps (FGPs) should be endoscopically followed up. Our findings showed that in the case of FGPs, yearly endoscopy is not required and it is sufficient to repeat X-ray and compare films with those obtained in the previous year. In contrast, yearly follow-up by endoscopy is necessary in the case of HPs.